Cellular mechanisms of acid secretion in the posterior midgut of the larval mosquito (Aedes aegypti) - Jagadeshwaran, U. (Company of Biologists, 2010)
The gut contents of larval mosquitoes are alkalinized by the anterior midgut and reacidified by the posterior midgut. In the present study the cellular mechanisms of reacidification were studied in isolated, perfused posterior midgut by measuring the transepithelial voltage (V(te)) and the rate of acid secretion as indicated by the color change of m-cresol purple during intervals of perfusion stop. The lumen-positive V(te) and reacidification were significantly increased by serotonin (0.2 μmol l(−1)). The V-type H(+)-ATPase inhibitor concanamycin A (10 μmol l(−1)) on the luminal side inhibited acidification and decreased V(te). On the hemolymph side the carbonic anhydrase (CA) inhibitor acetazolamide (1 mmol l(−1)) almost abolished V(te), but had no effect on acidification. Similarly, hemolymph-side DIDS (0.1 mmol l(−1)), DPC (0.5 mmol l(−1)), amiloride (1 mmol l(−1)) and ouabain (2.5 mmol l(−1)) significantly reduced V(te), whereas Ba(2+) (5 mmol l(−1)) was without effect. DPC and amiloride also reduced V(te) when applied to the luminal side of the epithelium. Unilateral substitution of gluconate for Cl(−) affected V(te) in a way consistent with a greater permeability for Cl(−) versus Na(+). Cl(−) replacement in the lumen decreased V(te), whereas replacement on the hemolymph side increased it. Bilateral replacement left the control voltage unaffected. Na(+) replacement on either side of the tissue reduced V(te) to different degrees. Omission of luminal amino acids was followed by a significant decrease in V(te). Except for concanamycin A, none of the above manipulations impaired acidification, indicating that acidification requires only the apical proton pump. However, the chemical source of secreted H(+) is still unknown and needs to be investigated.